Dragon's Blood Sap (Croton Lechleri) As Storage Medium For Avulsed Teeth: In Vitro Study Of Cell Viability - Martins,Christine Men (2016)
Abstract Tooth replantation success depends on the condition of cementum periodontal ligament after tooth avulsion; which is influenced by storage medium. The dragon's blood (Croton lechleri) sap has been suggested as a promising medium because it supports collagen formation and exhibits healing, anti-inflammatory and antimicrobial properties. Thus, the aim of this study was to evaluate the efficacy of dragon's blood sap as a storage medium for avulsed teeth through evaluation of functional and metabolic cell viability. This in vitro study compared the efficacy of different storage media to maintain the viability of human peripheral blood mononuclear and periodontal ligament cells. A 10% dragon's blood sap was tested while PBS was selected as its control. Ultra pasteurized whole milk was used for comparison as a commonly used storage medium. DMEM and distilled water were the positive and negative controls, respectively. The viability was assessed through trypan blue exclusion test and colorimetric MTT assay after 1, 3, 6, 10 and 24 h of incubation. The dragon's blood sap showed promising results due to its considerable maintenance of cell viability. For trypan blue test, the dragon's blood sap was similar to milk (p<0.05) and both presented the highest viability values. For MTT, the dragon's blood sap showed better results than all storage media, even better than milk (p<0.05). It was concluded that the dragon's blood sap was as effective as milk, the gold standard for storage medium. The experimental sap preserved the membrane of all cells and the functional viability of periodontal ligament cells.